Potential phosphorylation of Liprin-α1 at threonine 701 regulates integrin-mediated cell motility - Martina Ramella; Daniele Brambilla; Sara Surini; Diletta Tonoli; Lucrezia Maria Ribolla; Ivan de Curtis (PLoS ONE, 2025)
A dynamic protein network at the leading edge of motile cells is needed to coordinate events required for efficient cell motility. Previous work has shown that the Ser/Thr kinase DYRK3 affects the assembly of this network, and phosphorylates its component Liprin-α1, a scaffold protein regulating adhesion turnover and cell motility. We have looked for phospho-sites of Liprin-α1 relevant for the regulation of cell motility, by examining the role played by serine/threonine residues phosphorylated within the intrinsically disordered regions of Liprin-α1. Phospho-null mutations within either the amino-terminal or the carboxy-terminal disordered regions affect Liprin-α1 phosphorylation induced by DYRK3. Functional analysis shows that mutations within the amino-terminal region do not affect cell motility, while a set of carboxy-terminal mutations reduces the positive effects of Liprin-α1 on cell spreading on the extracellular matrix. Among several candidate phospho-sites in this protein region, we identify Thr 701 as one of the potential main targets of DYRK3 activity in Liprin-α1. The phospho-null mutation of Thr 701 specifically inhibits Liprin-α1–induced potentiation of cell spreading on fibronectin. Our findings contribute to highlight the complexity of the regulation of Liprin-αprotein functions by phosphorylation/dephosphorylation events. Given the involvement of Liprin-α proteins in tumor cell motility and invasion, in-depth understanding of this regulatory complexity may highlight new possibilities for therapeutic intervention.